MODEL KUALITAS LAYANAN DALAM MENENTUKAN KEPUASAN DAN LOYALITAS PASIEN DI RS MAYAPADA SURABAYA - Harry Purnomo, Salim; Oliandes, Sondakh (STIE PGRI Dewantara Jombang, 2025)
This study aims to analyze the influence of technical quality, procedural quality, infrastructural quality, interactional quality, personnel quality, and social support quality on patient satisfaction, as well as the influence of patient satisfaction on behavioral intention among inpatients at Mayapada Hospital Surabaya. The research method used is quantitative with a survey approach involving 240 inpatients. Data were analyzed using SPSS 22.0 through validity, reliability, normality tests, and linear regression analysis. The results show that technical quality, procedural quality, infrastructural quality, interactional quality, and personnel quality have a significant positive effect on patient satisfaction. Meanwhile, social support quality does not have a significant effect on patient satisfaction. Additionally, patient satisfaction has a significant positive influence on behavioral intention. These findings highlight the importance of improving the dimensions of technical service quality, procedural efficiency, facility infrastructure, interpersonal interaction, and healthcare personnel quality to enhance patient satisfaction and loyalty. This research is expected to contribute to the development of hospital service improvement strategies and enrich the academic literature in the field of healthcare service management.